Translation Procedures in Translating Abstracts of Postgraduate Students of Sultan Ageng Tirtayasa University - Dewata Carolia; Akhmad Baihaqi (Journal of English Language Teaching and Cultural Studies, 2019)
The research conducts to understand the translation procedures used in the translation of the thesis abstracts of postgraduate students. This research is qualitative. The data collected from students’ thesis abstract of Indonesia Language and Learning Technology programs. The result shows that there are five translation procedures applied, such  borrowing, calque, literal translation, transposition, and modulation; and the most dominant procedure used in translated thesis abstracts is literal translation with 9 sentences (32,14%), followed by modulation, borrowing and transposition with each of them is (17,85%), and the last is calque (14,28%).